A Review on Western and Chinese Organization Culture: Similarities and Differences - Qi, Jing Chun; Lee, Kar Ling (INTI International University, 2019)
The paper provides a literature review on organizational culture by analyzing the different dimensions between Western and Chinese organizational culture to ascertain whether there are similarities or differences. The purpose of selecting a comparative review of Western and Chinese organization culture is due to the rise of China as an economic power house whereby more and more companies are beginning to query whether a Western or Chinese organization culture would better serve the organization given today’s global landscape. This study focuses on Trompenaar’s cultural dimensions as a representation of the Western organization culture as the cultural model is considered to be the most comprehensive as compared to other Western organization culture and China’s Zhangde’s dimensions of organizational culture since the latter’s organization cultural dimensions are distinctly Chinese in nature. Applied emic-etic research method to combine the specific cultural items of organizational culture between Western and China are adopted as the research methodology which is qualitative in nature to determine whether a revised form of organizational culture model which is suitable for both the Western world and China’s company can be explored as the global economic power continues to shift to China.